Association of right ventricular dysfunction and pulmonary hypertension with adverse 30‐day outcomes in COVID‐19 patients. (1st April 2021) - Wats, Karan; Rodriguez, Daniel; Prins, Kurt W.; Sadiq, Adnan; Fogel, Joshua; Goldberger, Mark; Moskovits, Manfred; Tootkaboni, Mahsa Pourabdollah; Shani, Jacob; Jacob, Jessen
Abstract : Background: Cardiac manifestations in COVID‐19 are multifactorial and are associated with increased mortality. The clinical utility and prognostic value of echocardiography in COVID‐19 inpatients is not clearly defined. We aim to identify echocardiographic parameters that are associated with 30‐day clinical outcomes secondary to COVID‐19 hospitalization. Methods: This retrospective cohort study was conducted in a large tertiary hospital in New York City during the COVID‐19 pandemic. It included 214 adult inpatients with a laboratory‐confirmed diagnosis of COVID‐19 by reverse transcriptase polymerase chain reaction assay (RT‐PCR) for SARS‐CoV‐2 on nasopharyngeal swab and had a transthoracic echocardiogram performed during the index hospitalization. Primary outcome was 30‐day all‐cause inpatient mortality. Secondary outcomes were 30‐day utilization of mechanical ventilator support, vasopressors, or renal replacement therapy. Results: Mild right ventricular systolic dysfunction (odds ratio (OR): 3.51, 95% confidence interval (CI): 1.63–7.57, p = 0.001), moderate to severe right ventricular systolic dysfunction (OR: 7.30, 95% CI: 2.20–24.25, p = 0.001), pulmonary hypertension (OR: 5.39, 95% CI: 1.96–14.86, p = 0.001), and moderate to severe tricuspid regurgitation (OR: 3.92, 95% CI: 1.71–9.03, p = 0.001) were each associated with increased odds of 30‐day all‐cause inpatient mortality. Pulmonary hypertension and moderate to severe right ventricular dysfunction were each associated with increased odds of 30‐day utilization of mechanical ventilator support and vasopressors. Conclusions: Right ventricular dysfunction, pulmonary hypertension, and moderate to severe tricuspid regurgitation were associated with increased odds for 30‐day inpatient mortality. This study highlights the importance of echocardiography and its clinical utility and prognostic value for evaluating hospitalized COVID‐19 patients.